2021
DOI: 10.1088/1742-6596/1950/1/012084
|View full text |Cite
|
Sign up to set email alerts
|

Study and Trend Prediction of Covid-19 cases in India using Deep Learning Techniques

Abstract: The novel coronavirus or officially known as SARS-CoV 2 (Severe Acute Respiratory Syndrome Coronavirus 2) has caused a severe pandemic over the world affecting not only the economy of the countries but also the lifestyle of the people worldwide. As on 31.12.2020, Covid-19 (coronavirus disease) has infecting more than 10266674 people and causing about 148738 deaths in India. It has been seen through various statistics of various countries that the number of Covid-19 cases grows exponentially as the number of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Similar research [19] [20] demonstrated how random forest can be fine-tuned for a high dimensional dataset with large number of features relative to the sample size. Deep learning is one of the widely used that offers variety of models to deal with textual data analysis [21][22][23][24] and image classifications [25]. Deep neural network models, such as Convolutional Neural Networks, have shown great potential in image analysis and have emerged as a powerful tool for feature extraction and classification tasks [26][27][28].…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Similar research [19] [20] demonstrated how random forest can be fine-tuned for a high dimensional dataset with large number of features relative to the sample size. Deep learning is one of the widely used that offers variety of models to deal with textual data analysis [21][22][23][24] and image classifications [25]. Deep neural network models, such as Convolutional Neural Networks, have shown great potential in image analysis and have emerged as a powerful tool for feature extraction and classification tasks [26][27][28].…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…This is also called transfer learning. There are models that have already been trained, like VGG19 [31] and InceptionV3 [34]. Model extracts features from images by feeding them into models like VGG19 which had already been trained.…”
Section: Optimized Deep Convolutional Neural Network Modelmentioning
confidence: 99%
“…It entails employing methods like grid search or random search to get the ideal settings for the model's numerous hyper-parameters e.g., learning rate, number of filters in the convolutional layers, etc. [33][34][35].…”
Section: Hyper-parameter Tuningmentioning
confidence: 99%
“…There are several types of ANN, convolutional neural network (CNN) or deep neural network (DNN), recurrent neural network (RNN), and modular neural networks (MNNs) to name a few. A DNN or multilayer layer perceptron is based on ANN (Haleem et al, 2022; Shrivastava et al, 2021; Singhal et al, 2022; Wongchai et al, 2022). DNN is used for tasks like stock prediction, clustering problems, and weather prediction.…”
Section: Introductionmentioning
confidence: 99%